Leaf epidermal characteristics of medicinal Eclipta prostrata (L.) L., Vernonia amygdalina Delile (Asteraceae) and Clitoria ternatea L. (Fabaceae) - Nurshahidah Mohd Rusli,; Mohd Norfaizal Ghazalli,; Noraini Talip,; Samsiah Jusoh,; Razali Mirad,; Rosnani Abd. Ghani,; Wan Khairul Anuar Wan Ali,; Mohd Rani Awang,; Noor Ismawaty Nordin,; Ahmad Arif Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2021)
A study on leaf anatomical characteristics was undertaken on three medicinal plants species, Eclipta prostrata (L.) L., Vernonia amygdalina Delile and Clitoria ternatea L. It is found that there are variables in leaf epidermal features such as anticlinal wall patterns, stomata types, trichome types, and the occurrence of secretory structures. Results showed that there is slight variation in anticlinal wall patterns, which is, sinuous on abaxial surfaces and straight to wavy on adaxial surfaces of Eclipta prostrata, straight to wavy on both abaxial and adaxial surfaces of Vernonia amygdalina, and sinuous on both abaxial and adaxial surfaces of Clitoria ternatea, two types of stomata, which is anomocytic in Eclipta prostrata and Vernonia amygdalina, and paracytic in Clitoria ternatea, six types of trichomes recorded such as simple multicellular (short stalk – blunted tip), simple multicellular (echinate ornamentation, pointed tip), simple unicellular (echinate ornamentation, pointed tip), irregular T-shaped glandular (short to long stalk – elongated terminal), capitate glandular (short stalk – unicellular terminal) and peltate glandular. Secretory cells were observed in two species, Eclipta prostrata and Vernonia amygdalina. The leaf of these three medicinal species has been widely used in herbal preparation, however, there are not enough information nor a comprehensive study was done on the leaf anatomy of these species. Therefore, this study aimed to provide additional knowledge and more detailed information of the epidermal characteristics of Eclipta, Vernonia and Clitoria and contributes to systematic data available.